2001
DOI: 10.2139/ssrn.267534
|View full text |Cite
|
Sign up to set email alerts
|

How Do Stock Repurchases Affect Bank Holding Company Performance?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Some of them adopted new legislative rules to introduce these programs for the first time, like Japan in 1995 or Finland in 1997. Other countries approved some legislative changes to encourage firms to be more familiar with these programs like the United Kingdom in 2003 (Hirtle, 2001).…”
Section: Recent Developments In Stock Repurchase Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them adopted new legislative rules to introduce these programs for the first time, like Japan in 1995 or Finland in 1997. Other countries approved some legislative changes to encourage firms to be more familiar with these programs like the United Kingdom in 2003 (Hirtle, 2001).…”
Section: Recent Developments In Stock Repurchase Programsmentioning
confidence: 99%
“…We then matched this sample to Thomson Financial database, Worldscope and Compustat files with annual financial data available. To get more rigorous results and to conform with previous studies (Porter et al, 2000;Hirtle, 2001;Lamba and Ramsay, 2005), we withdrew all firms that had reported negative equity capital and firms involved in significant mergers during the sample period. The final selection allowed us to get relevant information for 200 firms.…”
Section: Data Source and Sample Descriptionmentioning
confidence: 99%